The Role of Risk Monitoring at Ar-Rifqi Integrated MI in Bolstering School Security - Jelita Citra Pertiwi; Wahyu Hidayat (Yayasan Zia Salsabila, 2024)
The purpose of this study is to investigate how Ar-Rifqi Integrated MI can enhance security through the use of risk monitoring. Education is seen as the cornerstone for developing the potential and character of the next generation, but its effectiveness depends not just on academic performance but also on the wellbeing of students and the safety of the learning environment. Today's educational institutions must contend with a growing number of intricate security issues, such as the possibility of cyberattacks, a lack of security knowledge, the possibility of human mistake, and unsafe data storage. Both positive and negative effects of technological advancements are present, including increased danger of cyberattacks and technological misuse. Thus, keeping an eye on hazards in schools is essential to preserving the security of information, facilities, and instructional activities. Along with defining the problem and the research objectives, this study engages parties and offers practical advantages in the form of in-depth insights, comprehension, and suggestions for enhancing the risk monitoring system and related party involvement. The goal of this research is to better understand and enhance the overall security of educational institutions.